Maternal allopurinol administration during suspected fetal hypoxia: a novel neuroprotective intervention? A multicentre randomised placebo controlled trial. Issue 3 (15th December 2014) - Kaandorp, Joepe J; Benders, Manon J N L; Schuit, Ewoud; Rademaker, Carin M A; Oudijk, Martijn A; Porath, Martina M; Oetomo, Sidarto Bambang; Wouters, Maurice G A J; van Elburg, Ruurd M; Franssen, Maureen T M; Bos, Arie F; de Haan, Timo R; et al.
Abstract : Objective: To determine whether maternal allopurinol treatment during suspected fetal hypoxia would reduce the release of biomarkers associated with neonatal brain damage. Design: A randomised double-blind placebo controlled multicentre trial. Patients: We studied women in labour at term with clinical indices of fetal hypoxia, prompting immediate delivery. Setting: Delivery rooms of 11 Dutch hospitals. Intervention: When immediate delivery was foreseen based on suspected fetal hypoxia, women were allocated to receive allopurinol 500 mg intravenous (ALLO) or placebo intravenous (CONT). Main outcome measures: Primary endpoint was the difference in cord S100ß, a tissue-specific biomarker for brain damage. Results: 222 women were randomised to receive allopurinol (ALLO, n=111) or placebo (CONT, n=111). Cord S100ß was not significantly different between the two groups: 44.5 pg/mL (IQR 20.2–71.4) in the ALLO group versus 54.9 pg/mL (IQR 26.8–94.7) in the CONT group (difference in median −7.69 (95% CI −24.9 to 9.52)). Post hoc subgroup analysis showed a potential treatment effect of allopurinol on the proportion of infants with a cord S100ß value above the 75th percentile in girls (ALLO n=5 (12%) vs CONT n=10 (31%); risk ratio (RR) 0.37 (95% CI 0.14 to 0.99)) but not in boys (ALLO n=18 (32%) vs CONT n=15 (25%); RR 1.4 (95% CI 0.84 to 2.3)). Also, cord neuroketal levels were significantly lower in girls treated with allopurinol as compared with placebo treated girls: 18.0 pg/mL (95% CI 12.1 to 26.9) in the ALLO group versus 32.2 pg/mL (95% CI 22.7 to 45.7) in the CONT group (geometric mean difference −16.4 (95% CI −24.6 to −1.64)). Conclusions: Maternal treatment with allopurinol during fetal hypoxia did not significantly lower neuronal damage markers in cord blood. Post hoc analysis revealed a potential beneficial treatment effect in girls. Trial registration number: NCT00189007, Dutch Trial Register NTR1383.